On the origins of gender roles: Women and the plough - Alberto Alesina; Paola Giuliano; Nathan Nunn (Institute for the Study of Labor (IZA), 2011)
This paper seeks to better understand the historical origins of current differences in norms and beliefs about the appropriate role of women in society. We test the hypothesis that traditional agricultural practices influenced the historical gender division of labor and the evolution and persistence of gender norms. We find that, consistent with existing hypotheses, the descendants of societies that traditionally practiced plough agriculture, today have lower rates of female participation in the workplace, in politics, and in entrepreneurial activities, as well as a greater prevalence of attitudes favoring gender inequality. We identify the causal impact of traditional plough use by exploiting variation in the historical geo-climatic suitability of the environment for growing crops that differentially benefited from the adoption of the plough. Our IV estimates, based on this variation, support the findings from OLS. To isolate the importance of cultural transmission as a mechanism, we examine female labor force participation of second-generation immigrants living within the US.
urn:nbn:de:101:1-201106013490
Keywords: D03; J16; N30; 330; culture; beliefs; values; gender roles